Transplantation of amniotic membrane for patients with bullous keratopathy and chemical and thermal burns - Siennicka, Agnieszka; Pecold-Stępniewska, Hanna; Czajka, Marcin (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
The aim of this paper is, to evaluate the efficacy of amniotic membrane transplantation for ocular surface reconstruction in patients with bullous keratopathy and chemical and thermal burns of cornea and conjunctiva. Amniotic membrane is a thin, semitransparent tissue forming an innermost layer of the fetal membrane, which contains a thick basement membrane with a single layer of epithelium and avascular matrix. This transplantation promotes normal conjunctival epithelization while suppressing fibrosis formation. Amniotic membrane transplant may be considered as an alternative method for treating ocular surface reconstruction in patients with thermal and chemical burns. Authors suggest that this method of treatment is not efficient in patients with bullous keratopathy.